Malaysian Politics in the New Media Age - Pooi Yin Leong, Pauline. author. aut Link
X, 169 p. 1 illus.
Keywords: This book provides a comprehensive overview of the impact of the emergence of the Internet on Malaysian politics and how it has played a pivotal role in influencing the country’s political climate. It lays out the background of Malaysia’s political history and media environment, and addresses the ramifications of media-ization on the political process, including political public relations, advertising and online campaigns. The book examines the Internet’s transformative role and effect on Malaysian democracy, as well as its consequences on political actors and citizenry, such as the development of cyber-warfare, and the materialisation of propaganda or “fake” news in the online domain. The book also investigates the interplay between traditional and new media on the progress of politics in Malaysia, especially as a watchdog on accountability and transparency, and contributes to current discourse on the climate of Malaysian politics as a result of the evolution of new media inthe country. This book is particularly timely in the wake of the 2018 Malaysian elections, and will be of interest to students and researchers in communications, politics, new media and cultural studies.